2020
DOI: 10.1108/ijhg-05-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Inter-professional physician-nurse collaboration in Lebanon

Abstract: PurposeA physician–nurse relationship is a complex, professional and shared-decision-making process, which is an important predictor of high-quality patient care. The purpose of this paper is to explore the attitude of the physician–nurse relationship in Southern Lebanon hospitals.Design/methodology/approachA descriptive institutional cross-sectional study was conducted among different departments of three hospitals in Southern Lebanon using a validated Jefferson Scale of Attitude.FindingsIn sum, 89 physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(35 reference statements)
0
2
0
1
Order By: Relevance
“…Hal ini bisa disebabkan karena kurangnya kejelasan peran dalam praktik kolaborasi (LaMothe et al, 2021). Padahal dalam penelitian di Libanon, perawat memiliki skor lebih tinggi dalam berkolaborasi (Ahmadieh et al, 2020).…”
Section: Pendahuluanunclassified
“…Hal ini bisa disebabkan karena kurangnya kejelasan peran dalam praktik kolaborasi (LaMothe et al, 2021). Padahal dalam penelitian di Libanon, perawat memiliki skor lebih tinggi dalam berkolaborasi (Ahmadieh et al, 2020).…”
Section: Pendahuluanunclassified
“…From Lebanon, Ahmadieh et al (2019) report on an area of conflict within the hospital sector. They suggested that effective and respectful physician–nurse collaboration is an indicator of care quality.…”
Section: Collaborative Working and Interprofessional Educationmentioning
confidence: 99%
“…Because of the cramped atmosphere of operating rooms, the personnel's having close contact with each other for a long time in the same room, the high pressure of work, doctors' tendency to make decisions without consulting the other members of the surgery team, nurses' limited autonomy, and ethical inequalities in the medial personnel's income and work privileges, the incidence of the above-mentioned consequences is higher in operating rooms (2,3,8,9). In many hospitals, the relationship between doctors and the other personnel is not satisfactory, leading to implicit or explicit verbal con icts and even physical ghts which, inevitably, have adverse effects on the doctors, the personnel and, by extension, the patients.…”
Section: Introductionmentioning
confidence: 99%